Factorise Display style X2 + Frac1X2 - 3

Given:

\( x^{2} + \frac{1}{x^{2}} – 3\) \( \Rightarrow x^{2} + \frac{1}{x^{2}} – 2 – 1\) \( \Rightarrow x^{2} + \frac{1}{x^{2}} – 2(x)(\frac{1}{x}) – 1\) \( \Rightarrow x^{2} + \frac{1}{x^{2}} – 2(x)(\frac{1}{x}) – 1\) \( \Rightarrow (x – \frac{1}{x})^{2} – 1^{2}\) \( \Rightarrow (x – \frac{1}{x} + 1) (x – \frac{1}{x} – 1) \)

Explore more such questions and answers at BYJU’S.

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question